Ataxia telangiectasia: what the neurologist needs to know. Issue 5 (21st September 2020) - Tiet, May Yung; Horvath, Rita; Hensiek, Anke E
Abstract : Ataxia telangiectasia is an autosomal recessive DNA repair disorder characterised by complex neurological symptoms, with an elevated risk of malignancy, immunodeficiency and other systemic complications. Patients with variant ataxia telangiectasia—with some preserved ataxia telangiectasia-mutated (ATM) kinase activity—have a milder and often atypical phenotype, which can lead to long delays in diagnosis. Clinicians need to be aware of the spectrum of clinical presentations of ataxia telangiectasia, especially given the implications for malignancy surveillance and management. Here, we review the phenotypes of ataxia telangiectasia, illustrated with case reports and videos, and discuss its pathological mechanisms, diagnosis and management.